Vprašanje vere in dvoma pri slovenskih protestantih (primer Primož Trubar) - Jensterle Doležal, Alenka (Slavia Centralis, 2020)
The Question of Faith and Doubt among Slovene Protestants (example Primož Trubar). This article analyzes the phenomenon of faith and doubt in two works of the Slovene protestant author Primož Trubar, the greatest Slovenian author of the 16th century: Ena dolga predguvor (1557) and Cerkovna ordninga (1564). In Trubar’s interpretation, faith is inherited; he understands it as a gift from God. The meaning of faith is focused through interpretation of the Bible. Faith is the main religious and ethical phenomenon; it presents man’s relation not only to God but also to society, and his relationship to existential, social, and moral reality. In Trubar’s, view the world is dual: it is divided into society with the right faith, and the condemned one, the society of others who live a lie, who don’t have the right faith. Doubt is the space of sin; it is the space without God’s mercy.
Keywords: the literature of Primož Trubar; the question of faith in Trubar´s literal work; Slovene reformation